Epidemiology and genotypic characterisation of dissemination patterns of uropathogenic Escherichia coli in a community. (2019) - Matsukawa, M.; Igarashi, M.; Watanabe, H.; Qin, L.; Ohnishi, M.; Terajima, J.; Iyoda, S.; Morita-Ishihara, T.; Tateda, K.; Ishii, Y.; Saga, T.; Aoki, K.; et al.
Abstract: To characterise the dissemination patterns of uropathogenic Escherichia coli (UPEC) in a community, we conducted a study utilising molecular and fundamental descriptive epidemiology. The subjects, consisted of women having community-acquired acute urinary tract infection (UTI), were enrolled in the study from 2011 to 2012. UPEC isolates were subjected to antibacterial-susceptibility testing, O serogrouping, phylotyping, multilocus-sequence typing with phylogenetic-tree analysis and pulsed-field-gel electrophoresis (PFGE). From the 209 unique positive urinary samples 166 UPEC were isolated, of which 129 were fully susceptible to the tested antibiotics. Of the 53 sequence types (STs), the four most prevalent STs (ST95, ST131, ST73 and ST357) accounted for 60% of all UPEC strains. Antimicrobial resistance was less frequently observed for ST95 and ST73 than for the others. A majority of rare STs and a few common STs constituted the diversity pattern within the population structure, which was composed of the two phylogenetically distinct clades. Eleven genetically closely related groups were determined by PFGE, which accounted for 42 of the 166 UPEC isolates, without overt geo-temporal clustering. Our results indicate that a few major lineages of UPEC, selected by unidentified factors, are disseminated in this community and contribute to a large fraction of acute UTIs.